A New Species of Moenkhausia Eigenmann, 1903 (Characiformes, Characidae) from the Upper Rio Negro Basin, Brazil - Soares, Isabel M. [UNESP]; Lima, Flávio C.T.; Bastos, Douglas A.; Py-Daniel, Lucia H. Rapp (American Society of Ichthyologists and Herpetologists (ASIH), 2019)
A new species of Moenkhausia is described from Rio Curicuriari and Rio Tiquié, both right-bank tributaries of the upper Rio Negro basin, Amazonas State, Brazil. The new taxon differs from all congeners, except M. agnesae and M. beninei, by the combination of a sinuous humeral blotch, similar to a compressed letter Z, and distinct dark longitudinal stripes along the body sides. The new species can be distinguished from M. agnesae and M. beninei by the presence of a single humeral blotch and of longitudinal stripes running through the center of the scales, more conspicuous dorsally.